DAMPAK KURS, SBI, INFLASI DAN INDEKS NIKKEI 225 TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Winda Wulandari; Deswita Herlina; Tony S Chendrawan (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study is to analyze the impact of exchange rate, SBI, inflation and nikkei 225 indexes on the composite stock price index in the Indonesian stock market. The data used in this study are time series data from the period of January 2013 to December 2017. This study uses the method of vector error correction model (VECM). The results of this study indicate that there is a causal relationship in which the variable that shows the originality is that there is a two-way relationship between inflation against SBI as well as a two-way relationship between SBI and inflation. Whereas the granger causality test can also show the existence of five one-way relationships including the Composite Stock Price Index to the Exchange Rate, the Composite Stock Price Index tothe Nikkei 225 Index, the Exchange Rate against SBI, the Exchange Rate to Inflation, and the Nikkei 225 Index to the Exchange Rate. In this study shows the long-term relationship between the Exchange Rate and Inflation variables show a positive effect on the composite stock price index while the SBI variable and the Nikkei 225 Index have a negative influence on the Composite Stock Price Index.The purpose of this study is to analyze the impact of exchange rate, SBI, inflation andnikkei 225 indexes on the composite stock price index in the Indonesian stock market.The data used in this study are time series data from the period of January 2013 toDecember 2017. This study uses the method of vector error correction model (VECM).The results of this study indicate that there is a causal relationship in which the variablethat shows the originality is that there is a two-way relationship between inflation againstSBI as well as a two-way relationship between SBI and inflation. Whereas the grangercausality test can also show the existence of five one-way relationships including theComposite Stock Price Index to the Exchange Rate, the Composite Stock Price Index tothe Nikkei 225 Index, the Exchange Rate against SBI, the Exchange Rate to Inflation, andthe Nikkei 225 Index to the Exchange Rate. In this study shows the long-termrelationship between the Exchange Rate and Inflation variables show a positive effect onthe composite stock price index while the SBI variable and the Nikkei 225 Index have anegative influence on the Composite Stock Price Index.